COLLABORATION BETWEEN GOVERNMENT AND CIVIL SOCIETY TOWARDS HANDLING SEXUAL VIOLENCE CASES IN SEMARANG CITY 2023 - Kamil, Laila Shafia Adzandien; -, Wijayanto -; Erowati, Dewi - (Journal of Politic and Government Studies, 2024)
This research discusses the collaborative process between the Semarang City Government and Civil Society towards handling cases of sexual violence in Semarang City in 2023. It aims to understand the strategies of each party in addressing sexual violence cases in Semarang City and to identify the success and inhibiting factors in the collaboration process between the Semarang City Government and Civil Society in handling cases of sexual violence in Semarang City in 2023. Additionally, from the perspective of governance collaboration, this research seeks to determine whether the collaborative process between the Semarang City Government and Civil Society aligns with existing theoretical concepts and achieves the expected goals. This research employs a descriptive research method with a qualitative approach. Data collection in this study involves in-depth interviews with head of Women’s Empowerment and Children’s Protection Department (DP3A) Semarang City, Head of Women’s and Children’s Protection Division of DP3A Semarang City, Head of UPTD PPA Semarang City, Director of LRC KJHAM, Head of Legal Aid Division of LRC KJHAM, Head of Policy Advocacy of LRC KJHAM, Head of Information and Documentation of LRC KJHAM, Unit PPA Polrestabes Semarang, and Sexual Violence Victim Advocate. As supporting data, this research utilizes literature review. The data analysis includes data reduction, data presentation, and conclusion drawing. The results indicate that the collaboration process between the Semarang City Government and Civil Society in handling cases of sexual violence in Semarang City has not been entirely successful. However, it has contributed to a shift in the public mindset, with more people now willing to report incidents of sexual violence and not viewing them as a disgrace. The research found there is no written binding agreement between the stakeholder involved in shared understanding indicator